Comprehensive circRNA expression profile and construction of circRNA‐associated ceRNA network in fur skin. Issue 3 (8th March 2018) - Zhu, Zhiwei; Li, Yuan; Liu, Wenyan; He, Junping; Zhang, Lihuan; Li, Huifeng; Li, Pengfei; Lv, Lihua
Abstract: Circular RNA (circRNA), a class of non‐coding RNAs, is a new group of RNAs that are related to tumorigenesis. The role of circRNAs in various diseases has been already highlighted. However, the expression levels and functions of circRNAs related to the melanocytes in the skin are poorly understood. RNA sequence was performed to analyse the expression profiles of circRNAs in black fur skin and white fur skin during different differentiation stages and investigate the relevant metabolism mechanisms. Differentially expressed circRNAs were detected using empirical Bayes sequencing (EBSeq) and then verified through the quantitative real‐time PCR method. The EQSeq analysis of circRNAs identified 11 downregulated and 32 upregulated circRNAs in the embryo of black fur skin and white fur skin, as well as 21 downregulated and 17 upregulated circRNA in the postnatal stage. A circRNA–microRNA (miRNA)–messenger RNA (mRNA) network was established to predict the circRNA targets. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were applied to enrich the mRNA data further. Results showed that the specific mRNAs mainly involved in the transcription‐related GOs, especially GO:0042802, GO:0005080 and GO:0032403, demonstrate their specific actions in transcriptional regulation. In the circRNA–miRNA–mRNA network, the most enriched GO terms of the mRNAs were pigmentation, protein autophosphorylation and protein complex. Therefore, the circRNA–miRNA–mRNA pathway may reveal novel mechanisms for pigmentation, and circRNAs may serve as candidates in pigmentation.